A hybrid biological and thermal waste-to-energy system with heat energy recovery and utilization for solid organic waste treatment. (1st June 2018) - Zhang, Jingxin; Kan, Xiang; Shen, Ye; Loh, Kai-Chee; Wang, Chi-Hwa; Dai, Yanjun; Tong, Yen Wah
Abstract: A hybrid biological and thermal waste-to-energy system in lab-scale level of application was developed to combine a 1000 L anaerobic digester and a 10 KW gasifier for solid organic wastes treatment and energy generation. Energy performance of the single system (anaerobic digestion (AD) and gasification) and the integrated AD – gasification system treating blended food waste (FW) and medium-sized woods chips (WCs) by cutting or chipping were studied. The results showed that the methane yield of AD of FW was 0.52 L CH4 /g VS/d with a volatile solid reduction rate of 85%. Producer gas with over 34% of CH4, H2, and CO was generated from gasification of WCs with biochar as a by-product. A small amount of the methane-rich gas generated from AD were mixed with a large amount of producer gas generated from gasification in a gas storage tank, improving the heating value of the producer gas. The waste heat generated from the gasification of WCs was used for the heat preservation of AD, increasing the overall energy efficiency of the integrated AD-gasification system. When the treatment capacity ratio of AD to gasification is below 0.4, the integrated AD - gasification system can operate with a self-supply heat recovery system. Highlights: Energy performance and potential benefits of a bio-and-thermal waste-to-energy system were studied. Anaerobic digester was integrated with gasifier for waste treatment and biogas/syngas generation. A 16%–54% higher heating value was achieved by mixing syngas and biogas for further utilization. Heat energy recycled from gasification was sufficient for the heat preservation of digester. The optimum energy efficiency of this integrated waste-to-energy system is 71.3%.